2016
DOI: 10.21315/mjms2016.23.6.10
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Patterns and Predictors of Poor Sleep Quality among Medical Students in King Khalid University, Saudi Arabia

Abstract: Background: Sleep problems and poor sleep quality are important issues for medical students. This study aimed to investigate the sleep patterns, measure the prevalence of poor sleep quality, and identify the predictors of poor sleep among medical students in King Khalid University (KKU), Saudi Arabia.Methods: This cross-sectional study enrolled 318 medical students during OctoberNovember, 2015. Participants were selected by convenience sampling and data were collected using self-administered questionnaires to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
8
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 19 publications
9
53
8
3
Order By: Relevance
“…Stratifying according to ethnicity revealed that minority students were more likely to report lower levels of sleep adequacy and sleep quantity and higher levels of sleep somnolence in a statistically significant way when compared with their Caucasian counterparts [41]. An even higher percentage was computed among students in Saudi Arabia, where poor sleep quality was reported by 74.2% of the study participants [42]. Percentages ranging from 58% to 77.78% were reported in other surveys [43][44][45].…”
Section: Discussionmentioning
confidence: 90%
“…Stratifying according to ethnicity revealed that minority students were more likely to report lower levels of sleep adequacy and sleep quantity and higher levels of sleep somnolence in a statistically significant way when compared with their Caucasian counterparts [41]. An even higher percentage was computed among students in Saudi Arabia, where poor sleep quality was reported by 74.2% of the study participants [42]. Percentages ranging from 58% to 77.78% were reported in other surveys [43][44][45].…”
Section: Discussionmentioning
confidence: 90%
“…The associations between gender and sleep disturbances have been controversial. For example, female students had a higher prevalence of sleep disturbances compared with male students in Peru and Pakistan (Sanchez et al ., ; Surani et al ., ), but the result was the opposite in Iran and Lebanon (Siddiqui et al ., ; Yazdi et al ., ), while no significant gender difference was found in the USA (Buboltz et al ., ). In this study, medical students (25.5%) were more vulnerable to sleep disturbances than non‐medical students (17.3%), which is consistent with previous findings (Shad et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies found variable rates of sleep disturbances in this population. The prevalence of sleep disturbances ranges from 3.0 to 74.2% worldwide, for instance, 3.0% in Thailand (Mohammadbeigi et al ., ), 9.8% in Lebanon (Younes et al ., ), 22.5% in the USA (Gress et al ., ), 33.3% in Japan (Supartini et al ., ), 74.2% in Saudi Arabia (Siddiqui et al ., ), 51.8% in Chile (Velez et al ., ), and 61.7% in Iran (Mohammadbeigi et al ., ). Apart from different sampling methods and geographic locations, the use of different instruments, such as the PSQI (Mohammadbeigi et al ., ), the Insomnia Severity Index (ISI; Gress et al ., ) and non‐quantitative measures (Peltzer and Pengpid, ) could account for such variation in prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…In King Saud College of Medicine, Riyadh, Saudi Arabia Abdulghani et al (2012) reported that 36.6% of medical students had poor sleep quality. Moreover, in King Khalid College of Medicine, Abha, Saudi Arabia, Siddiqui et al (2016) reported that poor sleep quality was claimed by 74.2% of medical students.…”
Section: Figure (1) Medical Students' Quality Of Sleep Discussionmentioning
confidence: 99%